Effect of type 2 diabetes mellitus on sperm quality and outcomes of assisted reproductive techniques in infertile male patients - Wang, Rui; Zhang, Yajuan; Li, Hui; Liu, Wanpeng; Xu, Lin; Lu, Meisong (Frontiers in Endocrinology, 2026)
BackgroundDiabetes mellitus (DM) is one of the most common endocrine disorders affecting various physiological systems and tissues, including the reproductive organs in men. However, the consequences of DM for male individuals undergoing assisted reproductive technology (ART) remain unclear.ObjectiveTo investigate the sperm quality and the outcomes of in vitro fertilization - embryo transfer (IVF-ET) and intracytoplasmic sperm injection - embryo transfer (ICSI-ET) in patients with type 2 diabetes mellitus (T2DM).MethodsWe retrospectively analyzed data from 318 infertile couples for IVF/ICSI cycle outcomes. The experimental group included 106 infertile couples (with male partners all diagnosed with T2DM) who underwent ART treatment at our center. The negative control group consisted of 212 non-diabetic infertile couples, matched by male/female body mass index (BMI) (± 1 kg/m²), male/female age (± 2 years), and serum anti-Müllerian hormone (AMH) levels (± 2 ng/mL). Patients were categorized into two groups based on clinical pregnancy. The χ² test and logistic regression analysis were used to identify and determine the influencing factors of clinical pregnancy.ResultsInfertile men with T2DM had significantly lower sperm volume (2.4 ± 2.2 vs. 2.7 ± 1.2, P < 0.01) and significantly decreased sperm motility compared to the control group (23.0 ± 17.2 vs. 29.7 ± 15.3, P < 0.01). In IVF/ICSI cycles, both groups exhibited similar results in two-pronuclear (2PN) fertilization rates and high-grade embryo rates (p > 0.05). The implantation rate, clinical pregnancy rate, and miscarriage rate also showed no significant differences (p > 0.05).ConclusionT2DM in infertile men exerts adverse effects on sperm quality; however, the decline in sperm quality did not translate into compromised clinical ART outcomes.